Historical blocking: RU 2022-02-21 to 2023-01-03 (Russia) - Voidly (Voidly Global Censorship Index, 2022)
CRITICAL severity censorship detected in Russia. Data sourced from ooni-historical-backfill.
Censorship Incident ID: RU-2022-0318. Severity: critical. Confidence: 95%